The think talk write type cooperative learning model assisted by serial picture media on the narrative writing skills of elementary school students - Alfiana, Vani Sella; Hutama, Fajar Surya; Nurdianasari, Nindya; Suhartiningsih, Suhartiningsih; Nugroho, Prasetyo Adi (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2024)
Writing skills are the most complex language skills and are very important for students to master in their learning process. The independent curriculum phase B states that students are expected to be able to write an essay, one of which is a narrative essay. Innovation in using various learning models is very much needed. The TTW-type cooperative learning model is appropriate to overcome the lack of students' writing skills. The study was conducted at Bangsalsari Public School 03 in Jember with the aim of determining the effect of the TTW-type cooperative learning model on the narrative writing skills of elementary school students. The type of research conducted was experimental research with a Posttest Only Control Group Design. The methods used were observation, interviews, performance tests, and documentation. The data analysis technique used the independent sample t-test. The results of the data analysis obtained a calculated t value > t table (6.696 > 2.004), so it can be concluded that the TTW-type cooperative learning model assisted by serial picture media influences the narrative writing skills of grade IV students at Bangsalsari Public School 03 Jember. Through narrative writing activities, students learn and develop critical and creative thinking skills, and they are trained to communicate directly with their peers, teachers, and themselves. This can help address the challenges of volatility, uncertainty, complexity, and ambiguity in the future.